The Effect of Reflective Learning Models with Realistic Mathematical Approaches with Keasyariahan Nuances on Mathematics Learning Outcomes - Nuari, Yuyun Rima; Assaibin, Muhammad; Febryanti, Febryanti (Journal of Mathematics and Applied Statistics, 2023)
This study aims to determine the effect of the reflective learning model with a realistic mathematical approach with religious nuances on the mathematics learning outcomes of Integral material students. The population in this study were all students of class XI IPS SMA Negeri 3 Polewali where the sample was taken by simple random sampling and taken by class XI IPS 4 as the experimental class and class XI IPS 1 as the control class. The instrument in this study was a learning achievement test consisting of pre-test and post-test and observation sheets consisting of student activity observation sheets and learning implementation sheets. The data obtained were analyzed using descriptive analysis and inferential analysis. The results of the descriptive analysis of mathematics learning outcomes in this case the post-test in both classes obtained an average value of 82.97 for the experimental class and 67.72 for the control class. The results of inferential analysis using the normality test and homogeneity test for both classes, namely the two classes are normally distributed and have homogeneous variance. From the results of descriptive analysis and inferential analysis, it can be concluded that the reflective learning model with a realistic mathematical approach with religious nuances has an effect on the mathematics learning outcomes of class XI social studies students at SMA Negeri 3 Polewali.